Key Ingredients of Anti-Stigma Programs for Health Care Providers: A Data Synthesis of Evaluative Studies. (January 2014) - Knaak, Stephanie; Modgill, Geeta; Patten, Scott B
Objective: As part of its ongoing effort to combat stigma against mental illness among health care providers, the Mental Health Commission of Canada partnered with organizations conducting anti-stigma interventions. Our objective was to evaluate program effectiveness and to better understand what makes some programs more effective than others. Our paper reports the elements of these programs found to be most strongly associated with favourable outcomes. Methods: Our study employed a multi-phased, mixed-methods design. First, a grounded theory qualitative study was undertaken to identify key program elements. Next, each program ( n = 22) was coded according to the presence or absence of the identified key program ingredients. Then, random-effects, meta-regression modelling was used to examine the association between program outcomes and the key ingredients. Results: The qualitative analysis led to a 6-ingredient model of key program elements. Results of the quantitative analysis showed that programs that included all 6 of these ingredients performed significantly better than those that did not. Individual analyses of each of the 6 ingredients showed that including multiple forms of social contact and emphasizing recovery were characteristics of the most effective programs. Conclusions: The results provide a validation of a 6-ingredient model of key program elements for anti-stigma programming for health care providers. Emphasizing recovery and including multiple types of social contact are of particular importance for maximizing the effectiveness of anti-stigma programs for health care providers.